Progressive MS trials: Lessons learned. (October 2017) - Tur, Carmen; Montalban, Xavier
Up to very recently, no treatments had proved effective in progressive multiple sclerosis (MS). In 2016, four drugs, two tested in phase 3 and two in phase 2 trials, showed a beneficial effect in primary or secondary progressive MS. Although this could indicate a turning point in progressive MS treatment, most of these successes have been modest and mainly restricted to patients with active inflammation, in the context of trials with powerful anti-inflammatory agents. This paper summarises these reasons, particularly focusing on the main lessons learned for the design of future trials. First, a drug's mechanism of action should tackle the specific pathogenic mechanisms that characterise progressive MS. Second, trial populations where new drugs are to be tested should be carefully chosen, possibly including younger patients with shorter disease durations, which have greater chances of showing active deterioration during the trial, therefore increasing the power to detect treatment effects. Third, outcome measures used in future phase 2 and phase 3 trials should be highly sensitive and be accompanied by smart trial designs.